Network Analysis and Legal Scholarship - Petersen, Niels; Towfigh, Emanuel V. (German law journal, 2017)
In their contribution in this issue Mattias Derlén and Johan Lindholm use social network analysis to show that the European Court of Justice is a precedent-driven constitutional court that is comparable to the US Supreme Court with regard to the citation of precedents. The article and its use of network analysis as a method provoked a lively debate on the editorial board of the German Law Journal about comparative law theory and methods generally and the place of empirical (including network) analyses in the comparative law discipline. For this reason, the editorial board commissioned this “special section” of contributions dedicated broadly to approaches to comparative law. In his essay in this section, for example, Jens Frankenreiter offers a detailed assessment of Derlén's and Lindholm's analysis. In this piece, we take a broader perspective and look at the utility and the limits of network analysis for legal scholarship generally.